DIAGNOSTICS AND EPISOTOTIC STATUS OF RABBIT EMERIOSIS IN CERTAIN DISTRICTS OF FERGANA REGION - Akhmadaliyev N.T; Khushnazarov A.Kh; Davlatov R.B (Western European Studies, 2024)
In this article, rabbits in farms specializing in modern rabbit breeding in Fergana city and Koshtepa districts of Fergana region were examined for eimerosis, and information on the extent and intensity of infestation in farms in these districts is presented
Keywords: Rabbit; eimeria; protozoa; apicomplexa